Enhancing the Brand Awareness of Tirta Sulung Water Refilling Station Through a Logo and a Flyer - Florencia Irene; Jusuf Imam Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
Tirta Sulung is a water refilling station established in Surabaya in 2009 and expanded to Jakarta in 2012. It offers standard refilled water and bio-energy water, with a focus on clean, healthy water using a biofiltration process. Despite its strengths, interviews with 25 potential and 35 existing customers revealed low brand awareness, mainly due to the lack of visual identity and promotional tools. To address this, the writer created a logo and a flyer based on branding theories by Vailukh et al. (2016), Prediger (2019), and Davis (2020), incorporating feedback from respondents. The logo features the brand’s name, product category, and a representative symbol to boost recognition and memorability. The flyer highlights the product’s unique selling points (USPs) as solutions to common issues with refilled water, aiming to build customer loyalty and a stronger competitive edge. Together, these tools are expected to significantly improve brand awareness.